PENGARUH PEMBERIAN DOSIS BOKASHI KELOR DAN BNR (Rhizoctonia binucleat) TERHADAP PERTUMBUHAN TANAMAN VANILI (Vanilla planifolia Andrews) - ismah Khoirunnisa; Teguh Supriyadi; Tyas Soemarah Kurnia Dewi; Agus Budiyono; Haryuni Haryuni (JURNAL ILMIAH AGRINECA, 2022)
Vanilla plant (Vanilla planifolia Andrews) is a spice plant that has high economic value. Vanilla growth is slow, so special treatment is needed so that its growth can be maximized. The purpose of this study was to determine the effect of giving Moringa bokashi and Binucleat-Rhizoctonia (BNR) on the growth of vanilla. The research was carried out at the Green House of Tunas Pembangunan University, Surakarta, Jl. Balekambang Lor No.1 at an altitude of 105 meters above sea level, on October 2019 - February 2020. This study used the factorial method with the basic pattern of Completely Randomized Block Design (RAKL) which consisted of 2 treatments with 3 replications. The first factor, Moringa bokasi dose (P) which consists of 4 levels, namely: P0: 50 g/plant, P1: 100 g/plant, P2: 150 g/plant, P3: 200 g/plant. While the second factor is: the dose of Rhizoctonia binucleate (R) which consists of 3 levels, namely: R0: 5 g/plant, R1: 10 g/plant, R2: 15 g/plant. Giving Moringa bokashi and BNR had a very significant effect on the number of leaves, and had a significant effect on plant height, and had no significant effect on the parameters of root length, fresh root weight, dry root weight, fresh stover weight and dry stover weight. The highest dry weight was found in the P3R0 treatment weighing 5.73 g and the lowest in the P2R1 treatment weighing 1.23 g.